Effect of castration and castration with hormone replacement on the plasma prolactin responses to neuroendocrine challenge with i.v. mCPP in the male rat following a low tryptophan diet. - Franklin, M; Craven, R; Cowen, P (1996)
Previous studies have shown that castration increased brain 5-HT synthesis and that sex steroid hormone treatment can reverse this effect. Tryptophan (TRP) depletion has been shown to reduce brain 5-HT synthesis and to cause the post-synaptic 5-HT receptors to up-regulate. We have studied the effects of castration and hormone replacement on the prolactin responses to neuroendocrine challenge with the post-synaptic 5-HT agonist, m-chlorophenylpiperazine (m-CPP) in male rats on a low TRP diet. Intact rats on a low TRP diet for 6 days showed significantly enhanced PRL reponses to mCPP as compared to intact rats on a complementary control diet. Animals castrated 20 days prior to neuroendocrine testing and on a low TRP diet demonstrated a loss of the enhanced PRL response to mCPP. The enhanced PRL response was restored by treatment with 25 mg/ kg of testosterone proprionate (TP) 24 h prior to testing. Rats treated with oestradiol benzoate (OB) from initial castration, showed significantly raised basal PRL concentrations but did not show enhanced PRL responses to mCPP in animals on either a low TRP diet or on a control diet as compared to castrated controls. It is suggested that castration increases brain 5-HT in these animals which leads to a down-regulation of post-synaptic 5-HT receptors. When the animals are then subjected to a low TRP diet for 6 days, a reduction in brain 5-HT synthesis occurs, causing a rebound up-regulation of the 5-HT receptors and therefore the end effect is a stalemate between the two initial effects resulting in the loss of the enhanced response. TP but not OB treatment in these animals restores the enhanced PRL response to mCPP by reducing brain 5 -HT synthesis and returning the post synaptic 5-HT receptors to a state of up-regulation.